2015
DOI: 10.1063/1.4905442
|View full text |Cite
|
Sign up to set email alerts
|

Integrated atomistic chemical imaging and reactive force field molecular dynamic simulations on silicon oxidation

Abstract: Evolution of structure, morphology, and reactivity of hydrogenated amorphous silicon film surfaces grown by molecular-dynamics simulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Recently, atomistic simulations have suggested that oxidation does not instantaneously yield SiO 2 . Rather a suboxide forms initially before gradually transforming to the dioxide phase [31][32][33]. Thus, there exists a transition layer with finite thickness between the unreacted silicon and fully reacted oxide, in which silicon exists in various oxidation states, i.e., Si + , Si 2+ , and Si 3+ [32].…”
mentioning
confidence: 99%
“…Recently, atomistic simulations have suggested that oxidation does not instantaneously yield SiO 2 . Rather a suboxide forms initially before gradually transforming to the dioxide phase [31][32][33]. Thus, there exists a transition layer with finite thickness between the unreacted silicon and fully reacted oxide, in which silicon exists in various oxidation states, i.e., Si + , Si 2+ , and Si 3+ [32].…”
mentioning
confidence: 99%
“…[1][2][3][4] In recent years, molecular dynamics simulations have been used to investigate the properties of polymers doped and modified by nanoparticles. [5][6][7][8][9][10][11][12][13] Simulations have demonstrated improvements in the mechanical properties of modified polymer materials, with the incorporation of smaller nanoparticles tending to yield larger increases in the Young's modulus. Incorporating nanoparticles can reportedly also improve the breakdown voltage and thermal stability of insulating materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the transition layer is also called suboxide layer. The XPS data also indicate that the ratio of the partially oxidized silicon atoms [Si(I), Si(II), Si(III)] is 1:2:3 for a‐SiO 2 /Si(100) interfaces and 1:2:1 for the a‐SiO 2 /Si(111), which may also be sensitive to sample preparation and probing techniques . The amorphous nature of a‐SiO 2 and the transition layer have challenged the modeling of the interfaces.…”
Section: Modeling A‐sio2/si Interfacementioning
confidence: 99%